Emotional transitions? Exploring the student experience of entering higher education in a widening-participation HE-in-FE setting. Issue 10 (25th November 2020) - Young, Emma; Thompson, Rachael; Sharp, John; Bosmans, Daniel
ABSTRACT: This paper details a small-scale research project that explores the student transition into higher education (HE), delivered in a further education college (FE), and considers whether the requirements of transition at this level impacts on emotional wellbeing. As such, it aims to contribute to the growing body of research on HE-in-FE from the perspective of student transition and emotional wellbeing. The data drawn on in this paper were collected by a questionnaire, administered at two points in the first semester, to measure levels of anxiety in students, alongside a further questionnaire designed to evaluate the effectiveness of bespoke academic skills input aimed at supporting the transition into HE. From quantitative and qualitative data, key findings identify factors that influence students' emotional responses to HE, including those that exacerbate an those that mitigate negative emotional responses. Significantly, the research identifies academic factors, rather than personal or social issues, as being critical to students' emotional experiences during the transitionary period.